2005
DOI: 10.1016/j.envpol.2005.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of sources and inflow of dioxins and polycyclic aromatic hydrocarbons from the sediment core of Lake Suwa, Japan

Abstract: To elucidate the historical changes in polychlorinated dibenzo-p-dioxin (PCDD), polychlorinated dibenzofuran (PCDF), coplanar polychlorinated biphenyl (co-PCB), and polycyclic aromatic hydrocarbon (PAH) inflows in Lake Suwa, their concentrations in the sediment core were analyzed in 5 cm interval. The maximum concentrations (depth cm) of PCDDs/DFs, co-PCBs, and PAHs were 25.2 ng/g dry (30-35 cm), 19.0 ng/g dry (30-35 cm), and 738, 795 ng/g dry (50-55 cm, 30-35 cm), respectively. Age and sedimentation rate of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 29 publications
4
19
0
1
Order By: Relevance
“…The PAHs contents are generally comparable to those in remote/rural or midsize city area. The average deposition flux of total PAHs (ng cm -2 year -1 ) in this study was higher than that in remote lakes (Gschwend and Hites, 1981), comparable to that in rural area (Ikenaka et al, 2005), and lower than that near urban area (Bixian et al, 2001;Latimer and Quinn, 1996) (Table 3).…”
Section: Contents and Deposition Fluxes Of Pahs In The Sediment Trap mentioning
confidence: 95%
“…The PAHs contents are generally comparable to those in remote/rural or midsize city area. The average deposition flux of total PAHs (ng cm -2 year -1 ) in this study was higher than that in remote lakes (Gschwend and Hites, 1981), comparable to that in rural area (Ikenaka et al, 2005), and lower than that near urban area (Bixian et al, 2001;Latimer and Quinn, 1996) (Table 3).…”
Section: Contents and Deposition Fluxes Of Pahs In The Sediment Trap mentioning
confidence: 95%
“…We used this data to evaluate spatial and species differences in heavy metal accumulation in the aquatic systems of Zambia. Lake sediments are often sampled to assess the level of environmental pollution (Ikenaka et al 2005a). In polluted aquatic systems sediments are increasingly recognized as the most important sink for contaminants and a future source of pollutants (Ikenaka et al 2005b).…”
mentioning
confidence: 99%
“…Flood as a natural disaster contributes in PAHs irregular concentrations where it washes out city surface to water bodies such as rivers and streams. Ikenaka et al, (2005) reported the highest PAHs of core layers with multiple pyrogenic sources from Lake Suwa, Japan when the heavy rain and consequently flood had been historically consistent. Discharges from natural disasters and local input are characterized by irregular distributions of PAHs.…”
Section: Wwwintechopencommentioning
confidence: 99%